Pressure-Induced Shifts in Trophic Linkages in a Simplified Aquatic Food Web - Schrama, Maarten; Barmentlo, S. Henrik; Hunting, Ellard R.; van Logtestijn, Richard S. P.; Vijver, Martina G.; van Bodegom, Peter M. (Frontiers in Environmental Science, 2017)
It is essential to understand effects of existing and emerging anthropogenic stressors on the structure of aquatic food webs in more natural settings, to obtain realistic predictions on how they can affect major ecosystem properties and functioning. We therefore examined whether 1) realistic concentrations of key agricultural pesticides and nutrients induce shifts in trophic linkages 2) observed changes in trophic linkages are qualitatively different between the green (algal-based) and brown (detritus-based) part of the food web. To this end, we exposed a simplified, yet realistic freshwater invertebrate community to environmentally relevant concentrations of three anthropogenic pressures (eutrophication; the herbicide terbuthylazine; and the insecticide imidacloprid) in a full factorial mesocosm design. Trophic linkages and the changes therein were assessed measuring stable isotopes of natural carbon and nitrogen. Results show that the green and brown part of the food web react qualitatively different to interacting pressures. Whereas herbivorous species react mainly to the nutrients and herbicides and the synergistic interaction between these, species in the detritivore part of the food web were affected by insecticide applications and interactions with nutrients. These results suggest that agricultural pressures can induce shifts in trophic linkages, but that they can have contrasting effects on the different parts of the food web. Such antagonistic and synergistic interactions can provide powerful explanations for observed responses of ecosystems to interacting stressors. These findings may have important implications for our understanding on interactions of agricultural stressors and their propagation in aquatic food webs.